Electromechanical Design of Self-Similar Inspired Surface Electrodes for Human-Machine Interaction - YongAn Huang; Wentao Dong; Chen Zhu; Lin Xiao (Complexity)
Stable acquisition of electromyography (EMG)/electrocardiograph (ECG) signal is critical and challenging in dynamic human-machine interaction. Here, self-similar inspired configuration is presented to design surface electrodes with high mechanical adaptability (stretchability and conformability with skin) and electrical sensitivity/stability which are usually a pair of paradoxes. Mechanical and electrical coupling optimization strategies are proposed to optimize the surface electrodes with the 2nd-order self-similar serpentine configuration. It is devoted the relationship between the geometric shape parameters (height-space ratio η, scale factor β, and line width w), the areal coverage α, and mechanical adaptability, based on which an open network-shaped electrode is designed to stably collect high signal-to-noise ratio signals. The theoretical and experimental results show that the electrodes can be stretched > 30% and conform with skin wrinkle. The interfacial strength of electrode and skin is measured by homemade peeling test experiment platform. The surface electrodes with different line widths are used to record ECG signals for validating the electrical stability. Conformability reduces background noises and motion artifacts which provides stable recording of ECG/EMG signals. Further, the thin, stretchable electrodes are mounted on the human epidermis for continuous, stable biopotential signal records which suggests the way to high-performance electrodes in human-machine interaction.